Prescribing of asthma medication in primary care for children aged under 10 - Schokker, Siebrig (Prim Care Respir J, 2010)
OBJECTIVE: To evaluate prescriptions of asthma medication for children in primary care. METHODS: Data on prescriptions of asthma medication for children aged 0–9 years were collected from a general practice-based network in the north eastern part of the Netherlands. Prevalence, incidence, indications, continuation beyond the age of 6 years, and predictors of continuation, were determined. RESULTS: Prevalence of prescriptions was about 80 per 1000 person years. An asthma diagnosis was registered in 40% of the children with a first prescription and in 70% of the children with six or more prescriptions. Discontinuation of asthma medication was between 60 and 90%. Continuation was more likely in children with a first prescription at age 2 or 3 as compared to children starting treatment at age ≤1 year. Children with prescriptions for β(2)-agonists and inhaled corticosteroids were more likely to continue treatment than children with β(2)-agonist monotherapy prescriptions. CONCLUSION: Continuation of asthma medication in children is low. Age at first prescription and the type of asthma medication are predictors of continuation of asthma medication from preschool into school-age.